Wholesale value uncovered: implementing effective marketing strategy and tactics to enhance customer perception - Scheetz, Dan M. (Kansas State University, 2015)
The Company is comprised of retail and w holesale agri-input outlets, toll/contract manufacturing and various departments that aid in three tiers of the supply chain. The Company Department 2’s principal goal is to earn a profit and that is achieved by helping their retail customers succeed across Division M. Therefore, a comprehensible strategy for selecting, positioning and promoting wholesale products and services is fundamental in uncovering actual value. The Company has grown to be one of the nation’s foremost agricultural distributors across the United States. Various geographies across the United States, excluding the region, have moved to a three-tier supply chain by merging retail and wholesale outlets. Currently, value demanded from end-users and retail outlets has been supplied from the wholesale level that has sustained the four-tier supply chain a cross the region of the United States. Even though the Company is vertically integrated, their knowled ge and core offerings originate from the retail segment of the supply chain. Retail firms that provide differentiated products and services with the most value to the end-user are those that fit the Company Department 2’s market. In addition, targeted retail fir ms emphasize a full-service business model by supplying produ cts and services across multip le categories. Company Department 2 provides value internally and externally. The three core areas from Company Department 2 are proprietary products, precision products and services, and other retail services valu able to retail customers. Positioning of these core areas differs based on the depth of the current relationship. A flanking strategy is proposed for prospective customers by bundling prestige goods and distribution innovations specifically in the focused proprietary line of products. A guerilla strategy is proposed for existing customers by highlighting product proliferation and improved services across all three of the core areas. Both strategies emphasize advertising and promotion, but more intensive campaigns are proposed with prospective customers. These positioning strategies and tactics are accomplished through accurate implementation at the field level. By risking a claim for what Company Department 2 stands for, communicating how value is created for a customer and communicating the reliability of these offerings, Company Department 2 will develop a unique identity in the marketplace.
Keywords: Wholesale; Strategy; Marketing; Tactics; Ag-input; Value